Longitudinal associations between depression and diabetes complications: a systematic review and meta‐analysis. Issue 12 (31st July 2019) - Nouwen, A.; Adriaanse, M. C.; van Dam, K.; Iversen, M. M.; Viechtbauer, W.; Peyrot, M.; Caramlau, I.; Kokoszka, A.; Kanc, K.; de Groot, M.; Nefs, G.; Pouwer, F.; et al.
Abstract: To conduct a systematic review and meta‐analysis of longitudinal studies assessing the bi‐directional association between depression and diabetes macrovascular and microvascular complications. Embase, Medline and PsycINFO databases were searched from inception through 27 November 2017. A total of 4592 abstracts were screened for eligibility. Meta‐analyses used multilevel random/mixed‐effects models. Quality was assessed using the Newcastle‐Ottawa scale. Twenty‐two studies were included in the systematic review. Sixteen studies examined the relationship between baseline depression and incident diabetes complications, of which nine studies involving over one million participants were suitable for meta‐analysis. Depression was associated with an increased risk of incident macrovascular (HR = 1.38; 95% CI: 1.30–1.47) and microvascular disease (HR = 1.33; 95% CI: 1.25–1.41). Six studies examined the association between baseline diabetes complications and subsequent depression, of which two studies involving over 230 000 participants were suitable for meta‐analysis. The results showed that diabetes complications increased the risk of incident depressive disorder (HR = 1.14; 95% CI: 1.07–1.21). The quality analysis showed increased risk of bias notably in the representativeness of selected cohorts and ascertainment of exposure and outcome. Depression in people with diabetes is associated with an increased risk of incident macrovascular and microvascular complications. The relationship between depression and diabetes complications appears bi‐directional. However, the risk of developing diabetes complications in depressed people is higher than the risk of developing depression in people with diabetes complications. The underlying mechanisms warrant further research. What's new?: Numerous studies have examined the longitudinal relationship between depression and diabetes complications but comprehensive evidence about the magnitude and direction is unavailable. The current study shows that the relationship between depression and diabetes complications appears bi‐directional with depression being associated with an increased risk of developing incident macrovascular and microvascular complications, and diabetes complications increasing the risk of subsequent depression. The increase in risk of developing diabetes complications in depressed people (by 38 and 33% for macrovascular and microvascular complications, respectively) is higher than the increase in risk of developing depression (by 9 and 24% for macrovascular and microvascular complications, respectively) in people with diabetes complications.